The Effect of Alpha-Tocopherol on the Expression of Epidermal Growth Factor Receptor and Transforming Growth Factor Beta Genes in Three Developmental Stages of Echinococcus granulosus - Seyyed Jafar NOSRATABADI; Nasim HAYATI ROODBARI; Mohammad Hossein MODARRESI; Alireza FARSINEJAD; Majid FASIHI HARANDI (Iranian Journal of Parasitology, 2020)
Background: In recent decades platyhelminths have been used as model organisms to address some of the fundamental questions related to the growth and development of animal organisms. Epidermal Growth Factor Receptors (EGFR) and Transforming Growth Factor beta (TGF-beta) have a regulatory role in the growth and development of Echinococcus species. This study determined the effect of alpha-tocopherol on the expression of EGFR and TGF-beta genes in three in vitro developmental stages of E. granulosus.